2014
DOI: 10.1186/1471-2458-14-1169
|View full text |Cite
|
Sign up to set email alerts
|

Social networks and mental health in post-conflict Mitrovica, Kosova

Abstract: BackgroundTo investigate the relation between social networks and mental health in the post-conflict municipality of Mitrovica, Kosovo.MethodsUsing a three-stage stratified sampling method, 1239 respondents aged 16 years or above were recruited in the Greater Mitrovica region. Social network depth was measured by the frequency of contacts with friends, relatives and strangers. Depression and anxiety were measured using the Hospital Anxiety and Depression Scale (HADS). Multivariate logistic regression was used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 46 publications
1
15
0
3
Order By: Relevance
“…Understanding the fact that it is essential, for mental health, to be able to preserve-post disaster or post conflict-one's relationship with a social network may be important to guide interventions in these contexts. In war-affected contexts in particular, specific types of networks may be beneficial for mental health, such as frequency of contact with friends 50 or being part of informal organizations (such as sports teams), whereas belonging to formal organizations such as church or unions may have the opposite effect. 49 These findings highlight the importance of differentiating between bonding, bridging, and linking in SC research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding the fact that it is essential, for mental health, to be able to preserve-post disaster or post conflict-one's relationship with a social network may be important to guide interventions in these contexts. In war-affected contexts in particular, specific types of networks may be beneficial for mental health, such as frequency of contact with friends 50 or being part of informal organizations (such as sports teams), whereas belonging to formal organizations such as church or unions may have the opposite effect. 49 These findings highlight the importance of differentiating between bonding, bridging, and linking in SC research.…”
Section: Discussionmentioning
confidence: 99%
“…50 The time elapsed between the conflict and the study ranged from 7 months 49 to 11 years. 50 The total data set was 3295 (median = 993, IQR: 2202-100). All studies focused on adults and were cross-sectional.…”
Section: Studies In Post-disaster Contexts Relating To Conflictmentioning
confidence: 99%
“…7 Other studies, which focused on specific regions of the country or specific subgroups, found a prevalence of depression which ranged from 29.7% to 66.5%. [8][9][10][11] It is clear that depression is common in Kosovo, far exceeding the global average. Some interpret the high rates of depression as an aftermath to the stressful conditions following the war.…”
mentioning
confidence: 99%
“…Se resalta que este estudió abordó un tema poco explorado, como es la reintegración de las personas pertenecientes a grupos al margen de la ley al ámbito laboral, ya que los estudios en población excombatiente se enfocan principalmente en las secuelas mentales que deja el conflicto armado, como depresión, ansiedad y estrés postraumático [31][32][33][34][35][36].…”
Section: Discussionunclassified